A further contribution to the knowledge of two inadequately known species of geophilid centipedes from the Andes of South-Central Chile, currently assigned to the genus Plateurytion Attems, 1909 (Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (Zootaxa, 2015)
Two poorly known species of geophilid centipedes from the Andes of South-Central Chile, i.e., Plateurytion mundus (Chamberlin, 1955) and Plateurytion zapallar (Chamberlin, 1955) (Myriapoda: Chilopoda: Geophilomorpha), are herein redescribed and illustrated after type specimens of both taxa and new material of the latter, rectifying the condition of the coxosternites of the second maxillae, which are medially joined through a narrow, hyaline and non-areolate membranous isthmus only (instead of “broadly fused as in Pachymerium”, as stated by Chamberlin), this being consistent with the current generic assignment of these species under Plateurytion Attems, 1909. New data on many morphological features of specific value, until now unknown, are also given for both taxa. Plateurytion zapallar is reported for the first time from Coquimbo region, 11 Km N of Los Vilos (Elqui province), Valparaíso region, Quebrada Huaquén, Pichicuy (Petorca province), La Campana National Park (Quillota province), and Quebrada el Tigre, Cachagua (Valparíso province). A key for identification of the South American species currently included in Plateurytion is given.